Ropes Made from “Lidah Mertua” Leaf Fiber - Detyara Imani; Lukman Adlin Harahap; Saipul Bahri Daulay (Jurnal Rekayasa Pangan dan Pertanian, 2016)
Fiber of Sansevieria has characteristics of not easily fragile, shiny, long, and good quality. This study was aimed to make and to examine the quality of rope made from “Lidah Mertua” leaf fiber (Sansevieria trifasciata laurentii). This research was conducted by literature study, spinning the rope using spinners simple tool, tensile test and parameters observation. Parameters measured were tensile strength, strain, elasticity, rope deformation, and flexing. Results of the research indicated that each substance tested with the same weight produced different string diameter. Average values of examinated ropes was 1,2 g weight, diameter was 4,26  mm, length was 34 mm, elongation was 17,2159 mm, maximum loaded was 659,2695 N, cross section was 14,31 mm2, elongation at break of tensile strength was 46,85 N/mm2, strain was 0,5063, elasticity was 92,5322 N/mm2, ropes deformation was 17,2159 mm and flexing was 50,63 %. Key words : Sansevieria, fiber ropes, natural fiber, tensile test